34. STUDY ON WAITING TIME FOR OUTPATIENT SERVICES AT THE TRADITIONAL MEDICINE INSTITUTE OF HO CHI MINH CITY AND RECOMMENDATIONS FOR IMPROVEMENT (Vietnam Journal of Community Medicine, 2025)
Background: Waiting time is a critical factor that affects service quality and patient satisfaction in outpatient care.Objective: To assess the current situation of outpatient waiting times at the Institute of Traditional Medicine in Ho Chi Minh City and propose directions for improving the clinical workflow.Methods: A cross-sectional study was conducted on 477 outpatients at the Department of Outpatient, Institute of Traditional Medicine, Ho Chi Minh City.Results: Male patients accounted for 56.19%. The average waiting time for the entire process was 44.00 ± 16.29 minutes. Waiting time increased with the number of indicateddiagnostic techniques: 34.35 ± 12.26 minutes (no technique), 40.80 ± 14.97 minutes (one technique), 47.24 ± 17.68 minutes (two techniques), and 53.61 ± 20.24 minutes (three techniques). Factors associated with longer waiting times included: first-time visits, health insurance coverage, morning consultations, and early weekdays. In contrast, patients using on-demand services had significantly shorter waiting times.Conclusion: Outpatient waiting times at the Institute generally met the Ministry of Health's standards. Ongoing review of workflows, patient stratification, and information technology application are essential to reduce waiting times and enhance service delivery effectiveness.
Keywords: Waiting time; outpatient care; Institute of Traditional Medicine.